Embryologic remnant of the umbilical vein presenting as an incarcerated umbilical hernia in a 6-month old: A case report - Blynn L. Shideler; Shelby R. Sferra; Roxanne L. Massoumi; Alexander V. Chalphin; Steven Stylianos (Elsevier, 2024)
Introduction: Incarcerated or strangulated pediatric umbilical hernias are uncommon but warrant urgent surgical intervention when present. Rarely, embryologic remnants can mimic an incarcerated umbilical hernia and may be indistinguishable on examination or imaging preoperatively. Case presentation: In this case report, a healthy 6-month-old male with a known persistent umbilical defect presented with one day of umbilical pain and physical examination consistent with hernia incarceration. The patient had a lack of obstructive symptoms and an abdominal X-ray with a non-obstructive gas pattern. However, an ultrasound was concerning for nonperistalsing bowel in the hernia defect. The patient was taken immediately to the operating room. Intraoperatively, there was no evidence of incarcerated bowel, but rather, an ischemic embryologic remnant. The hernia sac contents were excised and subsequently confirmed on surgical pathology to lack enteric or urologic mucosa and instead most consistent with a remnant of the umbilical vein. Conclusion: Overall, this case represents an interesting embryologic remnant mimicking an incarcerated umbilical hernia. This hernia likely benefited from surgical repair, serving as a reminder of the plethora of unanticipated rare hernia contents that can be present in pediatric surgery.